2022
DOI: 10.3389/fphar.2022.759247
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sodium Bicarbonate Infusion on Mortality in Critically Ill Children With Metabolic Acidosis

Abstract: Objective: Metabolic acidosis often occurs in the paediatric intensive care unit (PICU). Although sodium bicarbonate (SB) has been widely used in paediatrics, data on the effect of SB on children with metabolic acidosis in the PICU are scarce.Methods: Patients with metabolic acidosis who were treated with SB within 48 h of PICU admission were screened. Multivariate logistic regression, subgroup analysis, and propensity score matching (PSM) were used to investigate the relationships between SB infusion and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…In addition, based on curve analysis, we showed that the in-hospital mortality rate of the two groups of children with or without SB treatment gradually decreased with increases in the pH and HCO3concentration, but there was no signi cant difference in the inhospital mortality rate of the pH and HCO3concentration between patients with or without SB treatment. Based on the above results, we believe that although acidosis is associated with patient outcomes, SB treatment does not improve the overall outcome of patients in the PICU, which is in agreement to the results of other studies [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, based on curve analysis, we showed that the in-hospital mortality rate of the two groups of children with or without SB treatment gradually decreased with increases in the pH and HCO3concentration, but there was no signi cant difference in the inhospital mortality rate of the pH and HCO3concentration between patients with or without SB treatment. Based on the above results, we believe that although acidosis is associated with patient outcomes, SB treatment does not improve the overall outcome of patients in the PICU, which is in agreement to the results of other studies [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…Based on the real-world PICU database, we successfully showed that the in uencing factor, chloride concentration, affects the clinical outcome of metabolic acidosis in the treatment of SB. Similar studies used binary grouping, prior matching, or local subgroups to compare data [10,13,26]. Such an analysis method lacks a comprehensive exploration of the data, making it di cult to identify key factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, binary grouping, matching, or local subgroups were commonly utilized for comparative analyses of data [ 10 , 13 , 26 ]. However, these analytical methods are limited because they do not comprehensively explore the data information, making it difficult to identify factors that affect the clinical efficacy of SB.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is recommended to focus on treating the causes of metabolic acidosis rather than sodium bicarbonate infusion. 17 In their study, Takia et al, emphasized the need for a properly conducted trial to determine the role of IV soda bicarbonate therapy in treating severe acidosis, especially the NAGMA component, during the management of patients suffering from acute diarrhea and severe dehydration. Evidence-based guidelines on correcting metabolic acidosis and the indications of bicarbonate therapy may help critically ill pediatric patients.…”
mentioning
confidence: 99%